The significance of serum oligoclonal bands in neurological diseases. Issue 1 (January 1993) - Zeman, A; McLean, B; Keir, G; Luxton, R; Sharief, M; Thompson, E
Abstract : The presence of oligoclonal bands (OCBs) of immunoglobulin G (IgG) in CSF provides evidence for the occurrence of a humoral immune response, but it is not always appreciated that the oligoclonal IgG may have originated in the serum. To determine the diagnostic significance of serum OCBs 146 patients with serum OCBs were identified among 1874 patients with suspected neurological disorders (7.6%). Clear diagnoses had been made in 112 of these patients: in 56 identical CSF and serum bands were present, revealing a systemic immune response, while in 46 additional unique CSF bands indicated that intrathecal IgG synthesis was also occurring. In the first group neoplasia and peripheral neuropathies accounted for over 50% of the diagnoses, infections and systemic inflammatory disorders for 32%, and multiple sclerosis was diagnosed in only one case. These figures contrast considerably with those reported for patients with CSF OCBs alone. Diagnoses in the second group of patients, with unique CSF OCBs in addition to serum OCBs, resembled those among patients with CSF OCBs alone. Examining CSF and serum in parallel for OCBs of IgG provides more diagnostic information than examining CSF alone, and the latter is potentially misleading.